"If a (queer) revolt is to come": Toward a sensuous pedagogy for dis/orienting management learning. Issue 4 (September 2022) - Steyaert, Chris
This article embarks on a hopeful exploration of queer phenomenology in order to reorient management learning toward the senses, the body, and the spaces of learning and teaching we inhabit during education. Starting from Michel Serres' long-standing provocation that "If a revolt is to come, it will have to come from the five senses, " I ask whether and how we might reissue his timely call amid today's understandings of sensuous and embodied learning as the "conditions of arrival" have changed considerably since its first articulation. Therefore, I propose to queer such a sensorial revolt by turning to Ahmed's queer phenomenology as her understanding of dis/orientation as "the sixth sense" enables us to sensuously reorient management learning. To concretize and illustrate sensuous learning through dis/orientation, I draw on Fabian Ramos and Laura Roberts "pedagogy of wonder, " which forms part of their decolonial feminist educational work. In the epilogue, I introduce a new angle by revisiting Matthew Lopez's play The Inheritance and suggest that my queer attempt to refuse the inheritance of heteronormative learning and education also enables generations of diverse people to learn, in sensuous ways, from each other and from each other's otherness.